The Value of Glutathione-S-Transferase Gene Polymorphisms (GSTM1, GSTT1) in Various Inflammatory Phenotypes of Bronchial Asthma in Children - O.K. Koloskova; L.O. Bezrukov; T.M. Bilous; O.G. Grygola; Ye.P. Ortemenka (Zaslavsky O.Yu., 2014)
The aim of research: to study the peculiarities of a heterogeneous airway inflammation in children with bronchial asthma (BA) under the deletion polymorphism of GSTM1 and GSTT1 genes. Materials and Methods. We have examined 102 school-aged children with BA, of whom in 46 patients (I clinical group) the eosinophilic type of bronchial inflammation was verified, in 33 patients (II clinical group) - the neutrophilic type, and in 23 children (ІІІ group) - paucigranulocytic nature of inflammatory changes in the bronchi. Results. In patients with bronchial asthma, the homozygous deletion of GSTT1 gene has been detected in every fifth child, independently of type of airway inflammation. In patients with eosinophilic subtype of inflammation of the bronchi, GSTM1 gene deletion was noted in 32.6 % of cases, with neutrophilic one - in 51.1 % and with paucigranulocytic - 21.7 % of cases. In children with T1delM1+ genotype, severe BA in I group was detected in 37.5 % of cases, in the II - in 50.0 %, and in III group - in 100 % of cases (PIII : I,II < 0.05). Conclusions. Thus, children with different inflammatory phenotypes of asthma have certain characteristics of the disease course in the presence of GSTM1 and GSTT1 genes deletion polymorphism, which should be considered when choosing a treatment strategy in these patients.